2003
DOI: 10.3748/wjg.v9.i5.956
|View full text |Cite
|
Sign up to set email alerts
|

hOGG1 Ser326Cys polymorphism modifies the significance of the environmental risk factor for colon cancer

Abstract: AIM:To determine the association of hOGG1 (8-oxoguanine glycosylase I, OGG1) polymorphism of Ser326Cys substitution with colon cancer risk and possible interaction with known environmental risk factors. METHODS:A case-control study with 125 colon cancer cases and 247 controls was conducted. RESULTS:There was no major difference in Ser326Cys genotype distribution between cases and controls. The meat intake tended to increase the odds ratio for colon cancer with an OR of 1.72 (95 % confidence interval; CI=1.12-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 31 publications
5
61
1
Order By: Relevance
“…[8][9][10][11][12][13] The issue of whether the hOGG1 Ser326Cys polymorphism is associated with colorectal cancer remains controversial. 14,15 In the present study, we investigated whether the hOGG1 Ser326Cys polymorphism was associated with colorectal cancer risk by genotyping over 1,000 colorectal cancer patients and normal controls from the Korean population. In addition, we investigated whether the Ser326Cys polymorphism and colorectal cancer risk might be modulated by clinico-pathological characteristics such as tumor location, tumor-node-metastasis (TNM) stage or microsatellite instability (MSI) status.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13] The issue of whether the hOGG1 Ser326Cys polymorphism is associated with colorectal cancer remains controversial. 14,15 In the present study, we investigated whether the hOGG1 Ser326Cys polymorphism was associated with colorectal cancer risk by genotyping over 1,000 colorectal cancer patients and normal controls from the Korean population. In addition, we investigated whether the Ser326Cys polymorphism and colorectal cancer risk might be modulated by clinico-pathological characteristics such as tumor location, tumor-node-metastasis (TNM) stage or microsatellite instability (MSI) status.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of OGG1 activity in yeast is associated with a mutator phenotype that accumulates G:Cfito-T:A transversions. 24,25 Many epidemiological studies have investigated the association between the Ser326Cys polymorphism in the hOGG1 gene and the risk for different types of cancers, significant risk increases were observed for the hOGG1326polymorphism in the risk for esophageal, 26,27 orolaryngeal, 28 lung cancer, 29,30 colon cancer 31 and gastric cancer. 32,33 However, there are few reports about studying the association between gallbladder cancer and Ser326Cys hOGG1 polymorphism.…”
mentioning
confidence: 99%
“…had substantially lower DNA repair activity than that encoded by the 326Ser allele in an in vitro Escherichia coli complementation activity assay 14 and in human cells in vivo 15 whereas others did not find such a difference. 26,27 Thus, there is limited evidence of the genotype-phenotype relation, yet recent epidemiologic studies suggested that the putative low active allele (326Cys) was positively associated with lung, orolaryngeal, esophageal, stomach, and colon cancers, [16][17][18][19][20] but not with breast cancer. 28 To our knowledge, this is the first epidemiologic study on the association between the Ser326Cys polymorphism and HCC risk.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 The Ser326Cys polymorphism in exon 7 of hOGG1 has been related to glycosylase function and an individual's ability to repair damaged DNA. 14,15 Although recent studies [16][17][18][19][20] suggested that the low active hOGG1 allele (326Cys) was positively associated with the risk of several cancers while showing interactions with environmental factors, the association between this polymorphism and HCC has not been examined so far. Therefore, we conducted this case-control study including 209 HCC cases and two different controls (275 hospital controls and 381 patients with chronic liver disease [CLD] without HCC); CLD patients were selected as control subjects because most HCC patients in Japan have preexisting CLD.…”
Section: Serologic Tests and Genotypingmentioning
confidence: 99%